Recognizing the role of the vagus nerve in depression from microbiota-gut brain axis - Tan, Chaoren; Yan, Qiqi; Ma, Yue; Fang, Jiliang; Yang, Yongsheng (Frontiers in Neurology, 2022)
Depression is a worldwide disease causing severe disability, morbidity, and mortality. Despite abundant studies, the precise mechanisms underlying the pathophysiology of depression remain elusive. Recently, cumulate research suggests that a disturbance of microbiota-gut-brain axis may play a vital role in the etiology of depression while correcting this disturbance could alleviate depression symptoms. The vagus nerve, linking brain and gut through its afferent and efferent branches, is a critical route in the bidirectional communication of this axis. Directly or indirectly, the vagus afferent fibers can sense and relay gut microbiota signals to the brain and induce brain disorders including depression. Also, brain changes in response to stress may result in gut hyperpermeability and inflammation mediating by the vagal efferents, which may be detrimental to depression. Notably, vagus nerve stimulation owns an anti-inflammatory effect and was proved for depression treatment. Nevertheless, depression was accompanied by a low vagal tone, which may derive from response to stress and contribute to pathogenesis of depression. In this review, we aim to explore the role of the vagus nerve in depression from the perspective of the microbiota-gut-brain axis, highlighting the relationship among the vagal tone, the gut hyperpermeability, inflammation, and depression.